On Reading Poems: Visual & Verbal Icons in William Carlos Williams' «Landscape With The Fall Of Icarus» - Irene R. Fairley (Studies in 20th & 21st Century Literature, 1981)
Williams' admiration for Brueghel's landscape is coded in structural and stylistic correspondences between the poem and the painting. Structures in the poem have effects analogous to the use of devices of color, line, foregrounding in the painting. The poem, like the painting, presents a «neutral» scene but subtly insures the reader's involvement. Further, Williams draws a visual statement so that graphic features suggest a global image isomorphic with the motif of descent. Features of the poem, such as line and clause length, syntactic construction, semantic coherence, are discussed as factors that contribute to rapid glancing and increase readability. A study of readers shows their sensitivity to graphic features including the poem's shape, and corroborates the importance of stylistic features.
Keywords: Puerto Rican literature; American Poetry/ literature; Brueghel; poetry; painting; landscape; visual icons; verbal icons; comparison